Socialization of Coping in Pediatric Oncology Settings: Theoretical Consideration on Parent–Child Connections in Posttraumatic Growth - Koutná, Veronika; Blatný, Marek (Frontiers in Psychology, 2020)
This theoretical article aims to summarize the results of studies relevant to parental influence on coping with childhood cancer and provide implications for future research focused on parent-child connections in posttraumatic growth (PTG) following childhood cancer. Parental influence on child coping described by the socialization of coping and socialization of emotions theories has already been studied in connection with posttraumatic stress, but the role of parents in the process of PTG in the child has not been clearly described yet. Several studies focused on PTG in childhood cancer survivors and their parents simultaneously, but only two studies explicitly included a parent-child connection in PTG in statistical analysis. Studies suggest that child PTG may be facilitated through parental coping advice supporting emotion expression and that parent-child connection in PTG may be mediated by the child’s subjective perception of the parents’ PTG. More research is needed to describe specific strategies proposed by parents and leading to child PTG and design tailored interventions for the use in the clinical care of childhood cancer survivors and their family.